SENAM HAMIL METODE PILATES MENURUNKAN NYERI MUSKULOSKELETAL DALAM KEHAMILAN - Ika Oktaviani; Martini Martini (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2016)
Musculoskeletal complaint that often reported in third trimester pregnancy including back pain and waist pain. Others musculoskeletal complaint like rib pain, symphysis pain, if not get right handling, even the beginning as physiological changes but can impacted to phatological, like moving inability, hamper the supply nutrition to fetus. Can’t do per-vagina labor cause inability of relaxing when straining, and some other complications. Musculoskeletal disruption situation not only has correlation with shape and weight of mother. Pain complaint of musculoskeletal can’t be allowed without caring to decrease and solved it. Exercise along pregnancy can solve inconvenience in pregnancy. Superiority of pilates pregnancy exercise if compare to pregnancy exercise that have done that’s circulation exercise always do in every movement steps of pilates exercise. Pilates exercise is combine flexibility exercise, body strength, circulation and relaxation.